2018
DOI: 10.5614/j.eng.technol.sci.2018.50.1.6
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Structured Triglycerides Based on Canarium Oil for Food Application

Abstract: This paper concerns the synthesis of structured triglycerides containing different proportions and positions from medium-(M) and long-chain (L) fatty acids on a glycerol backbone. Structured triglycerides of MLM type were synthesized by utilizing canarium oil and incorporating caprylic acid (C8:0) as a source for the medium chain (M) fatty acids. Synthesis was performed through a two-step enzymatic reaction, with ethanolysis as the first step and esterification as the second step. Both reactions use the sn-1,3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…The purification of 2‐MAGs was achieved according to the method proposed by Johnner, Tutus, Kusnandar, Hamidah, and Tursino, () and Rodríguez et al () with some modifications. The mixture was extracted using ethanol:water (9:1 v/v) as solvent.…”
Section: Methodsmentioning
confidence: 99%
“…The purification of 2‐MAGs was achieved according to the method proposed by Johnner, Tutus, Kusnandar, Hamidah, and Tursino, () and Rodríguez et al () with some modifications. The mixture was extracted using ethanol:water (9:1 v/v) as solvent.…”
Section: Methodsmentioning
confidence: 99%
“…Next, the solution was added with 40 mL distilled water and 400 mL of n-hexane and the mixture was stirred again for 1 hour. The preparation of the solution was based on the description in Chen and Ju (2001) and Sitompul et al (2018). Further, separatory funnel was used to separate the results of the saponification reaction through solvent extraction.…”
Section: Preparation and Purification Of Free Fatty Acids (Ffa) By Sa...mentioning
confidence: 99%
“…The fatty acids were measured using HPLC based on the working procedure of Arcos et al (2000) and Sitompul et al (2018). This involved injecting 20 µL of the free fatty acids sample derivatized into the HPLC equipped with a UV detector at a wavelength λ=254 nm.…”
Section: Measurement Of Fatty Acids Composition Using Hplcmentioning
confidence: 99%
“…On the other hand, LCFAs located at sn -1,3 position are more likely to react with calcium to form soap ( 1 ). Stuctured lipids containing combinations of LCFA at sn -2 and MCFAs at sn -1,3 position, so-called medium-long-medium (MLM) TAG, will provide lipids with high coeficient absorption ( 14 , 15 ). It has been reported that MLM structured lipids have a low caloric value, and can be used to control obesity, fat malabsorption, and other metabolic disorders ( 2 , 16 18 ).…”
Section: Introductionmentioning
confidence: 99%